Examination of Group-Based Behavioral Skills Training for Parents of Children with Intellectual and Neurodevelopmental Disorders. Issue 2 (2nd April 2020) - LaBrot, Zachary C.; Kupzyk, Sara; Strong-Bak, Whitney; Pasqua, Jamie L.; Mahon, Jake
Abstract: Children with intellectual and neurodevelopmental disabilities are likely to present with behavioral and academic difficulties. Behavioral skills training to train parents to improve their children's outcomes has garnered a great deal of support for improving parents' use of evidence- based behavior management strategies. Unfortunately, children with intellectual and neurodevelopmental disabilities often experience behavioral health disparities due to lengthy wait lists for services. One solution for this problem is to train multiple caregivers in behavior management strategies at the same time. This study evaluated the effectiveness of group-based behavioral skills training for teaching parents of children with intellectual and neurodevelopmental disabilities to accurately implement effective instruction delivery and their children's response to instructions. Results indicated that parents' effective instruction delivery integrity improved and maintained over time, with concomitant improvements in children's response to instructions. Brief performance feedback was necessary for one parent to maintain increases in effective instruction delivery integrity. Results are discussed in terms of this study's outcomes, implications, and limitations.